The effect of catheter rotation during its withdrawal on frozen thawed embryo-transfer cycles outcomes: A Case-control study - Maryam Eftekhar; Lida Saeed; Masrooreh Hoseini (Shahid Sadoughi University of Medical Sciences, 2019)
Background Embryo transfer (ET) is the last and the most clinical process in assisted reproductive technology cycle. It has been suggested that cervical mucus interacts with an adequate embryo transfer in different ways. A few studies showed that catheter rotation could discharge mucus entrapped in the embryo to neutralize embryo displacement. Objective The aim of this present study was to compare the outcome of frozen embryo transfer (FET) based on catheter rotation during withdrawal. Materials and Methods In this case-control study, the clinical documents of 240 women who experienced frozen embryo transfer cycles were reviewd. The subjects were divided into two groups (n = 120/each), including A) the rotation treatment group (360°) that underwent ET using catheter rotation and B) the control group including the subjects who experienced ET with no catheter rotation. Clinical and chemical pregnancies and implantation rates were compared between two groups. Results Results showed that there is no significant difference between the basic clinical and demographic features of both groups (p > 0.05). A significant difference was observed in terms of the rate of chemical pregnancy between groups (21.7% vs 43.3%, p = 0.001 respectively). In addition, the rate of clinical pregnancy was significantly higher in study group than the control (33.35% vs 14.2%, p = 0.002 respectively). Conclusion Our results demonstrated that catheter rotation during withdrawal increased the implantation rate and clinical pregnancy.